Evolutionary optimization algorithms : biologically-Inspired and population-based approaches to computer intelligence - Simon, Dan, 1960- (New Jersey : John Wiley & Sons, Inc., 2013)
"This book is a clear and lucid presentation of Evolutionary Algorithms, with a straightforward, bottom-up approach that provides the reader with a firm grasp of the basic principles of EAs. Covering the theory, history, mathematics, and applications of evolutionary optimization algorithms, this timely and practical book offers lengthy examples, a companion website, MATLAB code, and a Solutions Manual--making it perfect for advanced undergraduates, graduates, and practicing engineers involved in engineering and computer science"--
"Provides a straightforward, bottom-up approach that assists the reader in obtaining a clear (but theoretically rigorous) understanding of Evolutionary Algorithms, with an emphasis on implementation rather than models"--
Includes bibliographical references (pages 685-726) and index.
Keywords: Evolutionary computation; Computer algorithms; Biologically-inspired computing; MATHEMATICS / Discrete Mathematics